Síntese e estudo da atividade antinociceptiva de Pep13, peptídeo derivado de PnTx4(6-1), uma toxina da peçonha da aranha Phoneutria nigriventer - Bruna Luiza Emerich Magalhães (2017)
The venom of the “armed” spider Phoneutria nigriventer has several biologically active peptides, one of them the toxin PnTx4(6-1) is a peptide composed of 48 amino acid residues and molecular mass of 5.2 kDa. PnTx4(6-1), also named δ-ctenitoxin-Pn1a, was initially described as a insecticidal neurotoxin, that binds to site 3 of sodium channels, in nerve cord synaptosomes of cockroach. When intracerebral injected in (30 μg) in mice, PnTx4(6-1) caused no apparent toxicity, moreover this toxin did not affect sodium channels of skeletal muscle (rSKM1) and brain (rBIIa), both of rats. Subsequently, we demonstrated that PnTx4(6-1) has antinociceptive effect in three pain models: i) inflammatory, evoked by carrageenan; ii) nociceptive, evoked by prostaglandin E2 and iii) neuropathic, evoked by constriction of the sciatic nerve. Using diverse receptors antagonists, we verified that the cannabinoid system, via the CB1 receptor, and the opioid system, through the μ and δ receptors, are both involved in the antinociceptive effect of PnTx4(6-1). In the present work, based on PnTx4(6-1) amino acid sequence we proposed and synthesized a linear peptide, with 13 amino acid residues named Pep13, based on the amino acid sequence of PnTx4(6-1) in order to try to reproduce or increase the analgesic effect of the toxin, with a simpler molecule. We verified, similarly to the toxin, the peptide has antinociceptive activity, when intrathecally administered, and this effect is also related to the cannabinoid and opioid systems. In addition, when the peripheral effect was evaluated, by intraplantar admistration, Pep13 was able to reverse the hyperalgesic threshold evoked by prostaglandin E2. Still related to the peripheral antinociceptive effect, the participation of the opioid system was observed, since the nonspecific antagonist (naloxone) was able to partially prevent the effect of Pep13. Regarding the cannabinoid system, by using specific antagonists, the participation of CB1 receptors was observed. Differently from the native toxin, which has a high toxicity to insects, the peptide caused no apparent effect when administered in flies. In conclusion, the synthetic peptide Pep13, which has 35 amino acid residues less than the native toxin PnTx4(6-1), reproduces the antinociceptive effects presented therein, without presenting however insect toxicity and may become a good model for new analgesics.